Preparation method of ruthenium dioxide-graphene-TALP thick and dense electrode

Through electrostatic self-assembly method and mechanical compaction technology, ruthenium dioxide and graphene are combined and TALP binder is added, which solves the problem that the existing technology cannot prepare thick electrodes, and achieves efficient preparation of supercapacitor electrodes.

CN119581242AActive Publication Date: 2025-03-07HEILONGJIANG INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411772133.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing methods cannot prepare ruthenium dioxide-graphene thick electrodes, limiting their application in supercapacitors.

Method used

Ruthenium dioxide was deposited on graphene nanosheets by electrostatic self-assembly, and the conductive adhesive TALP was added thereon. Ruthenium dioxide-graphene-TALP thick-density electrode was prepared by suction filtration and film formation and mechanical compaction.

Benefits of technology

It has achieved high volume specific capacity and high density electrode preparation, with a maximum mass specific capacity of 201F/g and a maximum volume specific capacity of 663F/cm3, and has excellent ultra-electric application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581242A_ABST
    Figure CN119581242A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ruthenium dioxide-graphene-TALP thick and dense electrode, and relates to a preparation method of a thick and dense electrode. The invention aims to solve the problems that the ruthenium dioxide-graphene thick and dense electrode cannot be prepared by the existing method, and the application of the ruthenium dioxide-graphene thick and dense electrode on a supercapacitor is limited to a certain extent. The preparation method comprises the following steps: 1, preparing TALP dispersion liquid; 2, performing ultrasonic dispersion treatment on the graphene nanosheets; 3, hydrolyzing to prepare a ruthenium dioxide-graphene nanosheet dispersion liquid; (4) preparing a ruthenium dioxide-graphene-TALP nanosheet dispersion liquid; and 5, performing mechanical compaction to prepare the ruthenium dioxide-graphene-TALP thick and dense electrode. The ruthenium dioxide-graphene-TALP thick and dense electrode prepared by the invention has the characteristics of high density and thickness, excellent conductivity, good volume capacitance performance and the like, and can be used as an electrode of a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a thick and dense electrode. Background Art

[0002] As one of the green and environmentally friendly high-efficiency energy storage devices, the performance of supercapacitors depends largely on the electrode materials used. In order to make the current electrochemical energy storage devices faster and lighter, the nano-size of electrode materials plays a vital role. However, due to the low stacking density of nano-size materials and relatively low volume performance, the device has a poor volume-to-capacity ratio, making it impossible to make the device smaller, which greatly limits its future application.

[0003] Among the various electrode materials, graphene has an ultra-high specific surface area (2630m 2 g -1 ), extremely high conductivity (10*6S·m -1 ), good thermal conductivity and mechanical properties, and is particularly suitable as energy storage materials, biomaterials, gas sensitive materials, superconductors and conductive additives. At present, the main methods for improving density are: capillary evaporation drying, liquid-mediated dense synthesis, three-dimensional porous structure processing and mechanical compaction.

[0004] Although capillary evaporation and liquid-mediated dense synthesis strategies can successfully prepare dense electrodes, the electrode thickness is too thin. The chemical activation pore-forming method has the disadvantages of low yield, small number of micropores and large pore size because the activator remaining on the surface of the material needs to be cleaned. Excessive pressure during mechanical compaction will cause the material to be deformed. Therefore, considering practical applications, it is necessary not only to design electrodes with high volumetric capacity, but also to take into account electrode density and electrode thickness. At present, there is no literature report on energy storage that takes into account surface loading, high volumetric capacity and high density at the same time. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the existing method cannot prepare ruthenium dioxide-graphene thick and dense electrodes, and the application in supercapacitors is limited to a certain extent, and to provide a method for preparing ruthenium dioxide-graphene-TALP thick and dense electrodes.

[0006] The present invention adopts a simple electrostatic self-assembly method to successfully anchor the ruthenium dioxide deposition onto the graphene nanosheets, adds a conductive adhesive TALP (tungstate linked polyaniline) thereon, and then prepares the ruthenium dioxide-graphene-TALP thick and dense electrode by the method of suction filtration film formation and mechanical compaction.

[0007] A method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode is specifically completed by the following steps:

[0008] 1. Preparation of TALP dispersion:

[0009] ①, dissolving aniline in aqueous sulfuric acid to obtain solution A;

[0010] ② Dissolve ammonium metatungstate and ammonium persulfate in deionized water to obtain solution B;

[0011] ③. Mix solution A and solution B, stir continuously for a period of time at room temperature, and then filter to obtain a solid substance; wash the solid substance, and then vacuum dry to obtain TALP powder; disperse the TALP powder in deionized water to obtain a TALP dispersion;

[0012] 2. Ultrasonic dispersion treatment of graphene nanosheets:

[0013] ①, dissolving sodium lignin sulfonate in deionized water to obtain a sodium lignin sulfonate solution; dispersing the graphene aqueous solution into the sodium lignin sulfonate solution under ultrasound, and ultrasonically dispersing for a period of time to obtain graphene nanosheets treated with sodium lignin sulfonate;

[0014] ②, washing the graphene nanosheets treated with sodium lignin sulfonate, and then dispersing them in deionized water under ultrasonic conditions, and ultrasonically dispersing them for a period of time to obtain a graphene nanosheet dispersion;

[0015] 3. Preparation of RuO2-Graphene Nanosheet Dispersion by Hydrolysis:

[0016] The RuCl3 aqueous solution is mixed with the graphene nanosheet dispersion, the temperature is raised to 310°C to 330°C, and then stirred and heated for a period of time under stirring and a temperature of 310°C to 330°C to obtain a ruthenium dioxide-graphene nanosheet dispersion;

[0017] 4. Preparation of RuO2-Graphene-TALP Nanosheet Dispersion:

[0018] Ultrasonic mixing the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion for a period of time to obtain a ruthenium dioxide-graphene-TALP nanosheet dispersion;

[0019] 5. Preparation of RuO2-Graphene-TALP Thick and Dense Electrode by Mechanical Compaction:

[0020] ① Filter the ruthenium dioxide-graphene-TALP nanosheet dispersion to form a membrane, then dry it, and then remove the filter membrane to obtain a membrane electrode;

[0021] ②. Heat treat the membrane electrode at a temperature of 140°C to 160°C for a period of time, and then compact it to obtain a ruthenium dioxide-graphene-TALP thick and dense electrode.

[0022] Advantages of the present invention:

[0023] 1. The present invention uses a simple electrostatic self-assembly method to successfully anchor ruthenium dioxide deposition onto graphene nanosheets, adds a conductive adhesive TALP thereon, and then prepares a ruthenium dioxide-graphene-TALP thick and dense electrode by suction filtration film formation and mechanical compaction. The process is simple and feasible, and the cost is low;

[0024] 2. The present invention introduces high-quality, high-conductivity, and adhesive TALP into ruthenium dioxide-graphene, thereby making up for the shortcoming that ruthenium dioxide-graphene itself cannot prepare thick and dense electrodes, and at the same time has excellent electrochemical performance; experimental results show that: at a current density of 1A / g, the maximum mass specific capacity is 201F / g, and the maximum volume specific capacity is 663F / cm 3 As a well-formed self-supporting electrode, it meets the practical requirements of ultra-high volumetric capacity and density, and has excellent prospects for superelectric applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a physical picture of the ruthenium dioxide-graphene and the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1, Figure 1 a is ruthenium dioxide-graphene, and b is the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0026] Figure 2 is a scanning electron microscope photograph and point scanning spectrum of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0027] Figure 3 is the X-ray diffraction pattern of TALP, ruthenium dioxide-graphene and ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0028] Figure 4 It is the transmission electron microscope spectrum and surface scanning spectrum of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0029] Figure 5 CV graphs of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 at different scanning rates;

[0030] Figure 6 It is the GCD diagram of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 at different current densities. DETAILED DESCRIPTION

[0031] Specific implementation method 1: This implementation method is a method for preparing a thick and dense ruthenium dioxide-graphene-TALP electrode, which is specifically completed in the following steps:

[0032] 1. Preparation of TALP dispersion:

[0033] ①, dissolving aniline in aqueous sulfuric acid to obtain solution A;

[0034] ② Dissolve ammonium metatungstate and ammonium persulfate in deionized water to obtain solution B;

[0035] ③. Mix solution A and solution B, stir continuously for a period of time at room temperature, and then filter to obtain a solid substance; wash the solid substance, and then vacuum dry to obtain TALP powder; disperse the TALP powder in deionized water to obtain a TALP dispersion;

[0036] 2. Ultrasonic dispersion treatment of graphene nanosheets:

[0037] ①, dissolving sodium lignin sulfonate in deionized water to obtain a sodium lignin sulfonate solution; dispersing the graphene aqueous solution into the sodium lignin sulfonate solution under ultrasound, and ultrasonically dispersing for a period of time to obtain graphene nanosheets treated with sodium lignin sulfonate;

[0038] ②, washing the graphene nanosheets treated with sodium lignin sulfonate, and then dispersing them in deionized water under ultrasonic conditions, and ultrasonically dispersing them for a period of time to obtain a graphene nanosheet dispersion;

[0039] 3. Preparation of RuO2-Graphene Nanosheet Dispersion by Hydrolysis:

[0040] The RuCl3 aqueous solution is mixed with the graphene nanosheet dispersion, the temperature is raised to 310°C to 330°C, and then stirred and heated for a period of time under stirring and a temperature of 310°C to 330°C to obtain a ruthenium dioxide-graphene nanosheet dispersion;

[0041] 4. Preparation of RuO2-Graphene-TALP Nanosheet Dispersion:

[0042] Ultrasonic mixing the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion for a period of time to obtain a ruthenium dioxide-graphene-TALP nanosheet dispersion;

[0043] 5. Preparation of RuO2-Graphene-TALP Thick and Dense Electrode by Mechanical Compaction:

[0044] ① Filter the ruthenium dioxide-graphene-TALP nanosheet dispersion to form a membrane, then dry it, and then remove the filter membrane to obtain a membrane electrode;

[0045] ②. Heat treat the membrane electrode at a temperature of 140°C to 160°C for a period of time, and then compact it to obtain a ruthenium dioxide-graphene-TALP thick and dense electrode.

[0046] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the volume ratio of the mass of aniline described in step 1① to the aqueous sulfuric acid solution is (0.9 g to 1.0 g): 50 mL; the concentration of the aqueous sulfuric acid solution described in step 1① is 0.2 mol / L. The other steps are the same as those in specific embodiment 1.

[0047] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the mass ratio of ammonium metatungstate described in step 1 ② to the volume ratio of deionized water is (2g-3g):50mL; the mass ratio of ammonium persulfate described in step 1 ② to the volume ratio of deionized water is (3g-4g):50mL. The other steps are the same as those of specific embodiment 1 or 2.

[0048] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the volume ratio of solution A to solution B in step 1 ③ is 1:1; the continuous stirring time in step 1 ③ is 22h to 26h. The other steps are the same as those in specific embodiments 1 to 3.

[0049] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 1 ③, water is used to wash the solid material 3 to 5 times; the vacuum drying temperature in step 1 ③ is 70°C to 80°C, and the vacuum drying time is 22h to 26h; the mass ratio of the TALP powder in step 1 ③ to the volume ratio of deionized water is 10mg:10mL. The other steps are the same as those in specific embodiments 1 to 4.

[0050] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that: the mass ratio of the sodium lignin sulfonate described in step 2① to the volume ratio of deionized water is (0.1g~0.3g):50mL; the mass fraction of the graphene aqueous solution described in step 2① is 2%~4%; the mass ratio of the sodium lignin sulfonate described in step 2① to the graphene aqueous solution is 1:(3~5); the power of the ultrasonic dispersion described in step 2① is 500W, and the ultrasonic dispersion time is 0.5h~1h. The other steps are the same as specific implementation methods 1 to 5.

[0051] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 2 ②, the graphene nanosheets treated with sodium lignin sulfonate are washed 2 to 4 times with deionized water; the mass of sodium lignin sulfonate described in step 2 ① and the volume ratio of deionized water described in step 2 ② is (0.1 g to 0.3 g): (20 mL to 30 mL); the ultrasonic dispersion time described in step 2 ② is 0.5 h to 1 h. The other steps are the same as those of specific embodiments 1 to 6.

[0052] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the concentration of the RuCl3 aqueous solution in step three is 0.1 mol / L; the volume ratio of the RuCl3 aqueous solution to the graphene nanosheet dispersion in step three is (15 mL to 20 mL): (20 mL to 30 mL); the stirring and heating time under stirring and temperature of 310° C. to 330° C. in step three is 5 h to 7 h. The other steps are the same as those in specific embodiments one to seven.

[0053] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the power of ultrasonic mixing described in step 4 is 900W, and the time of ultrasonic mixing is 5min to 10min; the volume ratio of TALP dispersion liquid to ruthenium dioxide-graphene nanosheet dispersion liquid described in step 4 is (9mL to 11mL): (80mL to 100mL). The other steps are the same as specific embodiments 1 to 8.

[0054] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the drying temperature in step 5① is 50℃~70℃; the heat treatment time in step 5② is 18h~20h; the compaction rate in step 5② is 30MPa / 1.54cm 2 The compaction time is 5 to 8 minutes. The other steps are the same as those in the first to ninth embodiments.

[0055] The following examples are used to verify the beneficial effects of the present invention:

[0056] Example 1: A method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode is specifically completed by the following steps:

[0057] 1. Preparation of TALP dispersion:

[0058] ①, dissolve 0.93g of aniline in 50mL of 0.2mol / L sulfuric acid aqueous solution to obtain solution A;

[0059] ② Dissolve 2.5g of ammonium metatungstate and 3.42g of ammonium persulfate in 50mL of deionized water to obtain solution B;

[0060] ③. Mix solution A and solution B, stir continuously for 24 hours at room temperature, and then filter to obtain a solid substance; wash the solid substance with deionized water for 5 times, and then vacuum dry it at 80°C for 24 hours to obtain TALP powder; disperse the TALP powder in deionized water to obtain a TALP dispersion;

[0061] The volume ratio of solution A to solution B described in step 1③ is 1:1;

[0062] The mass ratio of the TALP powder described in step 1 (3) to the volume ratio of deionized water is 10 mg:10 mL;

[0063] 2. Ultrasonic dispersion treatment of graphene nanosheets:

[0064] ①, dissolving 0.2g of sodium lignin sulfonate in 50mL of deionized water to obtain a sodium lignin sulfonate solution; dispersing 0.8g of a 3% graphene aqueous solution into the sodium lignin sulfonate solution under ultrasound, and ultrasonically dispersing for 0.5h at an ultrasonic power of 500W to obtain graphene nanosheets treated with sodium lignin sulfonate;

[0065] ②, washing the graphene nanosheets treated with sodium lignin sulfonate for 3 times, and then dispersing them into 25 mL of deionized water under ultrasonic conditions for 0.5 h to obtain a graphene nanosheet dispersion;

[0066] 3. Preparation of RuO2-Graphene Nanosheet Dispersion by Hydrolysis:

[0067] 17 mL of 0.1 mol / L RuCl3 aqueous solution was mixed with the graphene nanosheet dispersion, the temperature was raised to 320°C, and then stirred and heated at 320°C for 6 h to obtain a ruthenium dioxide-graphene nanosheet dispersion;

[0068] 4. Preparation of RuO2-Graphene-TALP Nanosheet Dispersion:

[0069] Ultrasonic mixing of the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion for 5 min to obtain a ruthenium dioxide-graphene-TALP nanosheet dispersion (the proportion of TALP is 10%);

[0070] The power of the ultrasonic mixing described in step 4 is 900W;

[0071] The volume ratio of the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion described in step 4 is 10 mL:90 mL;

[0072] 5. Preparation of RuO2-Graphene-TALP Thick and Dense Electrode by Mechanical Compaction:

[0073] ① Filter the ruthenium dioxide-graphene-TALP nanosheet dispersion to form a membrane, then dry it at 60°C, and then remove the filter membrane to obtain a membrane electrode;

[0074] ②, heat-treating the membrane electrode at 150°C for 19h, and then compacting it for 5min to obtain a ruthenium dioxide-graphene-TALP thick and dense electrode (TALP-RuO2-Graphene (10% TALP));

[0075] The compaction rate described in step 5② is 30MPa / 1.54cm 2 .

[0076] Example 2: The ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 was used as a working electrode for electrochemical testing. The specific operation is as follows:

[0077] The ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 was used as the working electrode, the Pt sheet was used as the counter electrode, Hg / Hg2SO4 was used as the reference electrode, and 1 mol / L H2SO4 solution was used as the electrolyte. The traditional three-electrode system was used to test the electrochemical properties of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 by cyclic voltammetry and constant current charge and discharge methods.

[0078] Figure 1 is a physical picture of the ruthenium dioxide-graphene and the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1, Figure 1 a is ruthenium dioxide-graphene, and b is the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0079] from Figure 1 It is obvious that the material can be compacted into a dense electrode only after adding TALP.

[0080] Figure 2 is a scanning electron microscope photograph and point scanning spectrum of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0081] from Figure 2 It can be seen that the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 is a sheet structure; the surface of the graphene nanosheet is smooth, the graphene sheet is thin and transparent, and the composite material contains elements such as C, O, Ru and W.

[0082] Figure 3 is the X-ray diffraction pattern of TALP, ruthenium dioxide-graphene and ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0083] Figure 3 The curve shows a diffraction peak corresponding to the graphene (002) crystal plane at 26.5°. The TALP diffraction peak also appears. Since ruthenium dioxide is amorphous, the diffraction peak is not obvious, but the presence of ruthenium can be clearly seen from the scanning electron microscope and the surface scanning of the transmission electron microscope, indicating that the composite material is composed of ruthenium dioxide, graphene and TALP.

[0084] Figure 4 It is the transmission electron microscope spectrum and surface scanning spectrum of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1;

[0085] The distribution of five elements, C, O, N, W and Ru, can be observed by scanning the surface under a transmission electron microscope. The HRTEM interlayer spacing is 0.479nm, and the material is judged to be TALP.

[0086] Figure 5 CV graphs of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 at different scanning rates;

[0087] from Figure 5 It can be seen that as the scan rate increases, the capacitance of the material decreases.

[0088] Figure 6 is the GCD diagram of the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 at different current densities;

[0089] from Figure 6 It can be seen that the ruthenium dioxide-graphene-TALP thick and dense electrode prepared in Example 1 has a mass specific capacity of up to 201F / g and a volume specific capacity of up to 663F / cm at a current density of 1A / g. 3 ; With the increase of rate, the performance can still be maintained well. At a high rate of 20A / g, the capacity is maintained at 217F / cm 3 ,from Figure 6 It is clearly observed that with the increase of current density, the volumetric capacity of the composite material decays accordingly, and the decay rate of the volumetric capacity is 32.8%.

Claims

1. A method for preparing a thick and dense ruthenium dioxide-graphene-TALP electrode, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of TALP dispersion: ①, dissolving aniline in aqueous sulfuric acid to obtain solution A; ② Dissolve ammonium metatungstate and ammonium persulfate in deionized water to obtain solution B; ③. Mix solution A and solution B, stir continuously for a period of time at room temperature, and then filter to obtain a solid substance; wash the solid substance, and then vacuum dry to obtain TALP powder; disperse the TALP powder in deionized water to obtain a TALP dispersion; 2. Ultrasonic dispersion treatment of graphene nanosheets: ①, dissolving sodium lignin sulfonate in deionized water to obtain a sodium lignin sulfonate solution; dispersing the graphene aqueous solution into the sodium lignin sulfonate solution under ultrasound, and ultrasonically dispersing for a period of time to obtain graphene nanosheets treated with sodium lignin sulfonate; ②, washing the graphene nanosheets treated with sodium lignin sulfonate, and then dispersing them in deionized water under ultrasonic conditions, and ultrasonically dispersing them for a period of time to obtain a graphene nanosheet dispersion; 3. Preparation of RuO2-Graphene Nanosheet Dispersion by Hydrolysis: The RuCl3 aqueous solution is mixed with the graphene nanosheet dispersion, the temperature is raised to 310°C to 330°C, and then stirred and heated for a period of time under stirring and a temperature of 310°C to 330°C to obtain a ruthenium dioxide-graphene nanosheet dispersion; 4. Preparation of RuO2-Graphene-TALP Nanosheet Dispersion: Ultrasonic mixing the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion for a period of time to obtain a ruthenium dioxide-graphene-TALP nanosheet dispersion; 5. Preparation of RuO2-Graphene-TALP Thick and Dense Electrode by Mechanical Compaction: ① Filter the ruthenium dioxide-graphene-TALP nanosheet dispersion to form a membrane, then dry it, and then remove the filter membrane to obtain a membrane electrode; ②. Heat treat the membrane electrode at a temperature of 140°C to 160°C for a period of time, and then compact it to obtain a ruthenium dioxide-graphene-TALP thick and dense electrode.

2. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The volume ratio of the mass of aniline described in step 1① to the aqueous sulfuric acid solution is (0.9g~1.0g):50mL; the concentration of the aqueous sulfuric acid solution described in step 1① is 0.2mol / L.

3. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The mass ratio of the ammonium metatungstate described in step 1② to the volume ratio of deionized water is (2g-3g):50mL; the mass ratio of the ammonium persulfate described in step 1② to the volume ratio of deionized water is (3g-4g):50mL.

4. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The volume ratio of solution A to solution B in step 1③ is 1:1; the continuous stirring time in step 1③ is 22h to 26h.

5. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that In step 1③, the solid material is washed with water for 3 to 5 times; the vacuum drying temperature in step 1③ is 70℃~80℃, and the vacuum drying time is 22h~26h; the mass ratio of TALP powder in step 1③ to deionized water is 10mg:10mL.

6. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The mass ratio of the sodium lignin sulfonate described in step 2① to the volume ratio of deionized water is (0.1g~0.3g):50mL; the mass fraction of the graphene aqueous solution described in step 2① is 2%~4%; the mass ratio of the sodium lignin sulfonate described in step 2① to the graphene aqueous solution is 1:(3~5); the power of the ultrasonic dispersion described in step 2① is 500W, and the time of ultrasonic dispersion is 0.5h~1h.

7. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that In step 2②, the graphene nanosheets treated with sodium lignin sulfonate are washed 2 to 4 times with deionized water; the mass ratio of the sodium lignin sulfonate described in step 2① to the volume ratio of the deionized water described in step 2② is (0.1 g to 0.3 g): (20 mL to 30 mL); the ultrasonic dispersion time described in step 2② is 0.5 h to 1 h.

8. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The concentration of the RuCl3 aqueous solution described in step three is 0.1 mol / L; the volume ratio of the RuCl3 aqueous solution described in step three to the graphene nanosheet dispersion is (15 mL~20 mL):(20 mL~30 mL); the stirring and heating time under stirring and temperature of 310°C~330°C in step three is 5h~7h.

9. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The power of the ultrasonic mixing in step 4 is 900 W, and the time of the ultrasonic mixing is 5 min to 10 min; the volume ratio of the TALP dispersion and the ruthenium dioxide-graphene nanosheet dispersion in step 4 is (9 mL to 11 mL): (80 mL to 100 mL).

10. The method for preparing a ruthenium dioxide-graphene-TALP thick and dense electrode according to claim 1, characterized in that The drying temperature in step 5① is 50℃~70℃; the heat treatment time in step 5② is 18h~20h; the compaction rate in step 5② is 30MPa / 1.54cm 2 The compaction time is 5min to 8min.

Citation Information

Patent Citations

  • Multifunctional lithium-sulfur battery diaphragm and preparation method thereof

    CN107887553A

  • Lamellar structure

    CN111095455A

  • Method for preparing graphene aqueous-phase dispersion liquid through mechanical stripping and graphene aqueous-phase dispersion liquid prepared through method

    CN113200538A

  • Preparation of intercalated conductive polymer / graphene oxide composite material and product and application of intercalated conductive polymer / graphene oxide composite material

    CN117143334A